PENGETAHUAN DAN PERSEPSI PERAWAT TENTANG TRIAGE DI UNIT GAWAT DARURAT RSUD KARAWANG - Rina Fera,; Wirdan Fauzi Rahmna, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The ER is a service provided to serve emergency patients with fast and standard treatment. The main standard that needs to be understood by nurses in providing services in the ER is related to Triage. So that the skills of nurses in applying the Triage concept are needed. The skill of a nurse in implementing triage is influenced by knowledge and also perception. Method: The type of research used by researchers is quantitative research with a descriptive research design. The sample in this study was 30 nurses who worked in the emergency room, who were selected by purposive sampling technique based on the inclusion and exclusion criteria of the researcher. These 30 respondents will be given triage knowledge questionnaires and questionnaires related to perceptions about triage whose results will be analyzed using Frequency Distribution. Results: 25 (83%) respondents had a good level of knowledge about triage and 30 respondents (100%) had positive perceptions about triage. Conclusion: The description of the knowledge of the Karawang Emergency Room nurse about triage is included in the good category with a positive perception of triage